Apoyo en la gestión de proyectos viales de la Alcaldía de Sogamoso (2024)
The document addresses an investigation to support the management of road projects in the Municipality of Sogamoso, with an emphasis on road network maintenance. It employs a mixed research approach combining qualitative and quantitative analyses, integrating theoretical knowledge with practical data related to road projects. The proposed methodology involves supervision and monitoring activities to ensure compliance with specifications in road projects. The aim is to comprehensively evaluate road network maintenance projects, demonstrating their conformity with specifications and providing information to enhance the effectiveness of future projects in Sogamoso.